(untitled) (Società e diritti, 2023)
The PNRR provides an opportunity to place social inclusion and the right to quality housing at the core of urban regeneration policies. The paper therefore aims, moving from the evolution of housing policies in the national framework, to provide a focus on the new model of urban transformation and to investigate whether and to what extent it constitutes the result of a globalized legal order in which goals and programs act as "rationalizing" and "civilizing" factors, orienting internal area policies towards a greater safeguarding of "social rights."